Penerapan Metode Wieghted SUM Model (WSM) Dalam Pengajuan Cuti Pegawai Rumah Sakit Bhayangkara Bengkulu - Lidya Anggraini; Dewi Suranti; Devi Sartika (Jurnal Media Infotama, 2025)
Bhayangkara Hospital Bengkulu is one of the privately owned public hospitals and is one of the type C hospitals in the Bengkulu region. Bhayangkara Hospital provides services in the field of leave applications to employees who want to apply for leave. So far, the employee leave application system is still manual and through a process that is not fast enough, where employees must seek approval from the hospital director and then submit the leave application form provided, therefore this leave application still cannot provide an opportunity for employees to apply for leave online. The decision support system (SPK) for leave applications using the Weighted Sum Model (WSM) method can be accessed online with internet access via the web link: https: //cutipegawairsbhayangkarabkl.online/. This decision support system application was created using the PHP programming language and MySQL database. The application has embedded the Weighted Sum Model (WSM) method which is used to apply for annual leave based on the criteria taken by employees. This application can assist in making decisions in applying for leave, employees can access the application starting from entering the Username and password to getting the results of the leave application whether the leave is accepted or not. Based on system testing that has been carried out, it can be concluded that the functional of the application has run well and this decision support system can provide results for leave applications based on the values and weights taken from employee criteria through the stages of the Weighted Sum Model (WSM) method.